Chondral and Osteochondral Femoral Cartilage Lesions Treated with GelrinC: Significant Improvement of Radiological Outcome Over Time and Zonal Variation of the Repair Tissue Based on T2 Mapping at 24 Months. (December 2021) - Schreiner, Markus M.; Raudner, Marcus; Szomolanyi, Pavol; Ohel, Kitty; Ben-Zur, Livnat; Juras, Vladimir; Mlynarik, Vladimir; Windhager, Reinhard; Trattnig, Siegfried
Objective: To prospectively assess the efficacy of GelrinC in the treatment of chondral and osteochondral femoral cartilage lesions using morphological (Magnetic Resonance Observation of Cartilage Repair Tissue [MOCART]) and quantitative (T2 -mapping) magnetic resonance imaging (MRI). Design: This study was designed as a prospective single-arm, open label, multicenter study. Morphological magnetic resonance imaging (MRI) for MOCART assessment and T2 mapping was performed 1 week and 6, 12, 18, and 24 months after GelrinC implantation. Evaluation of T2 mapping was based on the assessment of global T2 indices (T2 of the repair tissue [RT] divided by T2 of healthy reference cartilage) and zonal variation. Results: Fifty-six (20 female) patients were prospectively enrolled. The mean MOCART score significantly increased from baseline to the 24-month follow-up with 88.8 (95% CI, 85.8-91.9; P < 0.001) for all lesions combined as well as 86.8 (95% CI, 83.0-90.6) for chondral lesions and 94.1 (95% CI, 68.55-100) for osteochondral lesions. Furthermore, based on T2 mapping, significant zonal variation of the RT was observed at 24 months ( P = 0.039), which did not differ significantly from healthy reference cartilage ( P = 0.6). Conclusion: Increasing MOCART scores were observed throughout the follow-up period, indicative of maturation of the cartilage repair. Significant zonal variation of the RT at 24 months might indicate the transformation into hyaline cartilage–like RT. Slightly differing morphological outcome between chondral and osteochondral lesions, but similar global and zonal T2 indices at 24 months, support the potential of GelrinC as a treatment option for both lesion types.